The association of personality disorders with the prospective 7-year course of anxiety disorders - Ansell, E. B. (2010)
BACKGROUND: This study prospectively examined the natural clinical course of six anxiety disorders over 7 years of follow-up in individuals with personality disorders (PDs) and/or major depressive disorder. Rates of remission, relapse, new episode onset and chronicity of anxiety disorders were examined for specific associations with PDs. METHOD: Participants were 499 patients with anxiety disorders in the Collaborative Longitudinal Personality Disorders Study, who were assessed with structured interviews for psychiatric disorders at yearly intervals throughout 7 years of follow-up. These data were used to determine probabilities of changes in disorder status for social phobia (SP), generalized anxiety disorder (GAD), obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), panic disorder and panic disorder with agoraphobia. RESULTS: Estimated remission rates for anxiety disorders in this study group ranged from 73% to 94%. For those patients who remitted from an anxiety disorder, relapse rates ranged from 34% to 67%. Rates for new episode onsets of anxiety disorders ranged from 3% to 17%. Specific PDs demonstrated associations with remission, relapse, new episode onsets and chronicity of anxiety disorders. Associations were identified between schizotypal PD with course of SP, PTSD and GAD; avoidant PD with course of SP and OCD; obsessive-compulsive PD with course of GAD, OCD, and agoraphobia; and borderline PD with course of OCD, GAD and panic with agoraphobia. CONCLUSIONS: Findings suggest that specific PD diagnoses have negative prognostic significance for the course of anxiety disorders underscoring the importance of assessing and considering PD diagnoses in patients with anxiety disorders.